Effect of robot speed on cycle time and success rate in Automated Cover Assembly and Screwing - Adrianto, Raihan Nanda; Risfendra (Journal of Industrial Automation and Electrical Engineering, 2025)
This study investigates the effect of robot speed on cycle time and success rate in an automated cover assembly and screwing process. The experimental method was used to collect data by systematically varying the robot’s movement speed and observing its impact on performance metrics. Experiments were conducted on a six axis Epson C4 industrial robot integrated with a Siemens S7 1200 programmable logic controller (PLC). Robot speed was adjusted across ten predefined levels from 6% to 33% of maximum velocity in 3% increments and for each level, three repeated trials were executed under controlled conditions. Results show that increasing speed from 6% to 33% reduces average cycle time from 908.6 s to 503.6 s for 4 product (227,1s–125,9s per product), a 44.6% improvement in efficiency. The relationship between speed and success rate is nonlinear: moderate speeds (27%–30%) yield an optimal success rate of 93.75% with cycle times of 517 s–533 s for 4 product (129s–133s per product), whereas both lower and maximum speeds decrease reliability due to vacuum pickup misalignment and screw retrieval inconsistencies. These findings underscore the need to balance speed and precision to optimize both efficiency and reliability in robotic assembly systems